Ontology-Based Technology for Development of Intelligent Scientific Internet Resources - Zagorulko, Yury; Zagorulko, Galina (Intelligent Software Methodologies, Tools and Techniques, 2015)
The paper discusses the main features of a technology for the development of subject-based Intelligent Scientific Internet Resources (ISIR) providing content-based access to systematized scientific knowledge and information resources related to a certain knowledge area and to their intelligent processing facilities. An important merit of ISIR is its ability to reduce appreciably the time required to access and analyze information thanks to the accumulation of the semantic descriptions of the basic entities of a knowledge area being modeled, the Internet resources relevant to this area, and the information processing facilities (including web-services) used in it directly in the ISIR content. The specific features of the technology are the use of ontology and semantic network formalisms and orientation to experts, i.e. specialists in the knowledge areas for which ISIR are built.